Twelve month prospective study of snakebite in a major teaching hospital in Mandalay, Myanmar; Myanmar Snakebite Project (MSP). (January 2019) - White, Julian; Alfred, Sam; Bates, David; Mahmood, Mohammad Afzal; Warrell, David; Cumming, Robert; Thwin, Khin Thida; Thein, Myat Myat; Thant, Myo; Naung, Zaw Myo; Naing, Ye Htet; San, Su Sint Sint; et al.
Abstract: The Myanmar Snakebite Project is an Australian government (Department of Foreign Affairs and Trade) supported foreign aid project in collaboration with the Myanmar government with the aim of improving outcomes for snakebite patients in Myanmar. As part of the project a case record database was established to document prospective cases of snakebite presenting to Mandalay General Hospital, in Upper Myanmar. The study period was 12 months (1-2-2016 to 31-1-2017). Snake identity was based on a mixture of identified dead snakes brought with patients, doctor's clinical opinion and patient identification. 965 patients were enrolled during the 12 month period, of whom 948 were included for analysis. The male: female ratio was 1.58:1. Most cases involved bites to the lower limbs (82.5%) and adults involved in farm work, confirming snakebite as an occupational disease in this community. Motorised transport was by far the most common form of transport to health care and most patients sought care from the health system (87.7%), not traditional healers (11.5%) as their first point of contact. The officially promoted application of a pressure pad, bandage and immobilisation as first aid for snakebite was almost never used, while most patients used some form of tourniquet (92.0%). 85.4% of cases where a snake ID was listed were bitten by Russell's vipers. Russell's viper bites were responsible for all fatalities (9.8% of cases) and all cases of Acute Kidney Injury (AKI). For all cases, clinical features included local swelling (76.5%), local pain (62.6%), AKI (59.8%), incoagulable blood (57.9%), regional lymphadenopathy (39.8%), nausea/vomiting (40.4%), thrombocytopenia (53.6%), abdominal pain (28.8%), shock (11.8%), secondary infection (8.6%), panhypopituitarism (2.1%). AKI required renal replacement therapy (RRT) in 23.9% of cases, all ascribed to Russell's viper bite. Green pit viper bites were the next most common cause of bites (7.6%) and were associated with incoagulable blood (29%) and occasionally shock (5%) and local necrosis (3%), and in one case AKI not requiring RRT. In contrast to Russell's viper bites, green pit viper bite was most likely to occur in the home (49%). Some green pit viper patients were treated with Russell's viper antivenom (15%), presumably because they had incoagulable blood, although this antivenom is not effective against green pit viper envenoming. For the entire patient group, antivenom was given in 80.5% of cases. The most common indications were presence of coagulopathy/non-clotting blood (59.8%), local swelling (47.4%), oliguria/anuria (19.8%), heavy proteinuria (19.4%). A febrile reaction to antivenom was reported in 47.9% of cases, while anaphylaxis, occurred in 7.9% of cases. Highlights: Reports 12 month prospective observational study of snakebite patients at Mandalay General Hosp. Snakebite was an occupational disease of farm workers, tourniquets the most common first aid. Russell's viper (RV) responsible for most bites, causing coagulopathy, thrombocytopenia, AKI. Green pit viper bites were the next most common, potentially causing diagnostic confusion with RV.